Nanostructured Materials for Treating Aquatic Pollution - Gonçalves, Gil Alberto Batista; Marques, Paula (Engineering Materials,, 2019)
This book report the advances in the synthesis of new nanomaterials for the remediation of natural waters, groundwaters, and wastewaters. The authors describe synthetic routes for the assembly of different nanomaterials for the removal of contaminants by adsorption, catalytic degradation, and antibacterial activity. The hazardous effects of nanomaterials in aquatic ecosystems are discussed. This book presents the trends in the development of advanced technologies available in the market based on nanomaterials for more efficient water remediation. The authors also discuss sustainable management of water resources according to the new technologies developed and the improved efficiency of remediation processes.